1996
DOI: 10.1152/ajpendo.1996.271.3.e439
|View full text |Cite
|
Sign up to set email alerts
|

Presence of renin within intramitochondrial dense bodies of the rat adrenal cortex

Abstract: It has been suggested that tissue-specific expression of the genes of the renin-angiotensin system (RAS) leads to local generation of angiotensin (ANG) II with specific physiological implications. We demonstrate here that an intracellular RAS exists in adrenal glomerulosa cells; 60 h after bilateral nephrectomy and hemodialysis, renin and prorenin were eliminated from the circulation, whereas intra-adrenal renin content increased (control rats: 2 +/- 0.5 ng ANG I.mg-1.h-1; anephric rats: 25 +/- 2). Thus renin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 24 publications
6
71
2
Order By: Relevance
“…Evidence has indicated a direct interaction between angiotensin II and mitochondrial components [42][43][44][45]. In a study using 125 I-labeled angiotensin II in rats, angiotensin II was detected in the mitochondria and nuclei of the heart, brain and smooth muscle cells [42,43].…”
Section: Angiotensin II and Mitochondrial Functionmentioning
confidence: 99%
“…Evidence has indicated a direct interaction between angiotensin II and mitochondrial components [42][43][44][45]. In a study using 125 I-labeled angiotensin II in rats, angiotensin II was detected in the mitochondria and nuclei of the heart, brain and smooth muscle cells [42,43].…”
Section: Angiotensin II and Mitochondrial Functionmentioning
confidence: 99%
“…However, our purpose was not to pursue these differences, but to identify a tissue storing only Con A non-binding renin, as this could indicate cells lacking a specific glycosyl transferase for mannose, or possibly possessing a mannose removing glycosidase. 5 While this study has not identified a tissue 25 and is presumably not glycosylated, because, although coded by nuclear DNA, it lacks a signal for entry into the endoplasmic reticulum. 26 This form of tissue renin may be a truncated amannosylated prorenin, 26 but would not be expected to be secreted into plasma at consistent levels, either before or after incorporation into mitochondria.…”
Section: Discussionmentioning
confidence: 86%
“…This way Ang II may stimulate an increase in mitochondrial oxidative stress, thus leads to VCMC senescence. Also, mitochondria may endogenously produce Ang II [36][37][38]. Several animal studies show that Ang II causes and contributes to aortic endothelial dysfunction [39][40][41].…”
Section: Role Of Ras In Atherosclerosis Developmentmentioning
confidence: 99%